Transcendental Structuralism Perspective on Teacher Professional Ethics (Review on Al-‘Alaq 1-5) - Rahayu Subakat; Suwarno Suwarno; Moh. Isbir (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2021)
Philosophically, Q.S. Al-'Alaq 1-5 forms an ethical structure as the foundation for developing the teaching profession in Islamic education. The theoretical claim in this study is Q.S. al-'Alaq 1-5 was elaborated with the theory of transcendental structuralism, resulting the structure of professional ethics. In addition, the theory of professional ethics for teachers can be used as a theoretical framework to analyze the problems of teachers as educators in general. The aims of this study are to explain the relationship between Q.S. al-'Alaq 1-5 with the ethics of the teaching profession, to describe the form of the structure of professional ethics in Q.S. al-'Alaq 1-5 and to clarify the implementation of the professional ethics structure of Q.S.al-'Alaq 1-5 teachers in Islamic education. In addition, the research method used in this research is library research. It is conducted by collecting and reading literature to find theoretical concepts using the constructivist paradigm and the hermeneutic approach of transcendental structuralism. Furthermore, source of data for this study are based on the Koran and interpretation; classic, modern, and contemporary. Data is analysed using content analysis. It is by analyzing the message content of the letter Al-'Alaq verses 1-5 and Kuntowijoyo's prophetic social theory. Finally, the result of this study shows that the structure of the professional ethics of teachers based on Q.S. Al-'Alaq 1-5 is about the relationship between spiritual, rational, ethical, scientific, and social transformation awareness.